Comparison of Saans neonatal continuous positive airway pressure against standard of care for intra-hospital transport of neonates with respiratory distress syndrome - ., Jagadeesh; Singh, Megha; M. S., Bhavana; ., Kavitha; Chander, Ravi (International Journal Of Community Medicine And Public Health, 2021)
Background: CPAP (continuous positive airway pressure) therapy, effective in managing neonates with respiratory distress. While CPAP therapy is indicated right from birth, existing CPAP systems are designed for/installed in, NICUs. As a result, most neonates with RD (respiratory distress) are managed with only oxygen therapy during transportation in low resource settings. This study compares a novel, low-cost, portable neonatal CPAP system for use in transport from the labor room to the NICU, against conventional oxygen therapy in low resource settings. Methods: This was an open-label, 2 arm study with a treatment arm (low-cost indigenous CPAP device for therapy) and a control group (oxygen therapy). A total of 132 neonates were assigned with 66 in (matched-control study), in each group. Results: Both arms (CPAP and oxygen) had similar gestational age. gender distributions and initial SAS scores. The CPAP group had higher use of antenatal steriods (38 versus 26) compared to oxygen group and a lower need for surfactant (28 versus 40). Also, a larger number of neonates required ventilation in oxygen group (42) versus CPAP group (15), with the p=0.000561 the result is significant at p<0.05. Conclusions: CPAP therapy induced in labor room measurably improves neonates health and reduces respiratory distress. The indigenous low-cost CPAP device (Saans) used in this study effectively provides CPAP therapy to neonates during transport from the labor room to the NICU, reducing respiratory distress and the need for mechanical ventilation, making useful addition to labor rooms.